A multi-degree-of-freedom triboelectric energy harvester for dual-frequency vibration energy harvesting. (1st April 2023) - Liu, Zicheng; Zhao, Chaoyang; Hu, Guobiao; Yang, Yaowen
Abstract: Vibrational energy harvesting based on triboelectric transduction has been proven to be a cost-effective solution for powering small electronic sensors. Triboelectric energy harvesters (TEHs) that work in the contact-separation mode have been widely investigated with beam-mass structures. However, most beam-based TEHs utilize cantilever beams as their driving component, which is applicable only when its first mode is excited because higher modal frequencies are usually beyond the range of ambient vibrations. This study presents a novel contact-separation-mode energy harvester that, for the first time, combines triboelectric transduction with a multi-degree-of-freedom (MDOF) L-shaped beam-mass structure to harvest vibration energy at two operating frequencies. The TEH proposed in this study has two operating frequencies under 20 Hz and thus possesses an increased operating frequency range. A fully coupled electromechanical model that combines an MDOF distributed-parameter mechanical model with an electrical model for the TEH is derived. Experiments are then carried out to validate the model, characterize the performance of the TEH, and investigate the effect of the MDOF beam-mass structure on the contact-separation-mode TEH. It is shown that the predictions of the electromechanical model have an overall good agreement with the experimental results. Besides, the TEH can achieve a maximum root-mean-square voltage of 9.45 V when the first mode is excited and 11.56 V when the second mode is excited, given a base excitation acceleration of 0.6 g and the external load resistance of 1 MΩ. An optimal power of 300 μW is realized when the external load is 85 MΩ.